2020
DOI: 10.1111/ajo.13146
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal vaccine uptake: A cross‐sectional study investigating factors influencing women’s choices in pregnancy

Abstract: Background: Seasonal influenza and pertussis cause significant morbidity and mortality among expectant mothers and infants. Vaccination during the antenatal period is an important public health intervention, minimising rates of maternal, neonatal and infant infection. Aims: The primary aim of this project was to establish the rates of antenatal vaccine uptake. Secondly, the study aimed to determine socio-demographic factors significant to vaccine uptake. Thirdly, the project aimed to produce a thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A large cross-sectional study designed to monitor rates of prenatal vaccination found higher rates of pertussis vaccination when compared with influenza. 85 Maternal preference to select vaccinations with a perceived benefit to their child, versus one that confers a benefit to themselves in addition to negative perceptions for the influenza vaccine, might contribute to lower adherence rates when compared with pertussis and combination Tdap vaccination. 86,87 Gains, Gaps, Challenges, and the Future Since the concept of general maternal immune suppression during pregnancy as a means of immune tolerance toward the fetus was first postulated more than 50 years ago, 88 an impressive body of knowledge has accumulated, and the field has seen major advances in elucidating immune processes at play in maintaining maternal tolerance of fetal antigens and immune homeostasis, their disturbances, and resulting inflammation and immune dysregulation.…”
Section: Vaccination Against Maternal and Fetal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large cross-sectional study designed to monitor rates of prenatal vaccination found higher rates of pertussis vaccination when compared with influenza. 85 Maternal preference to select vaccinations with a perceived benefit to their child, versus one that confers a benefit to themselves in addition to negative perceptions for the influenza vaccine, might contribute to lower adherence rates when compared with pertussis and combination Tdap vaccination. 86,87 Gains, Gaps, Challenges, and the Future Since the concept of general maternal immune suppression during pregnancy as a means of immune tolerance toward the fetus was first postulated more than 50 years ago, 88 an impressive body of knowledge has accumulated, and the field has seen major advances in elucidating immune processes at play in maintaining maternal tolerance of fetal antigens and immune homeostasis, their disturbances, and resulting inflammation and immune dysregulation.…”
Section: Vaccination Against Maternal and Fetal Infectionsmentioning
confidence: 99%
“…A large cross-sectional study designed to monitor rates of prenatal vaccination found higher rates of pertussis vaccination when compared with influenza. 85 Maternal preference to select vaccinations with a perceived benefit to their child, versus one that confers a benefit to themselves in addition to negative perceptions for the influenza vaccine, might contribute to lower adherence rates when compared with pertussis and combination Tdap vaccination. 86 , 87 …”
Section: Vaccination Against Maternal and Fetal Infectionsmentioning
confidence: 99%
“…The Advisory Committee on Immunization Practices of the Centre for Disease Control in the USA currently recommends vaccination in pregnancy for Influenza and Tetanus, diphtheria and pertussis (https://www.cdc.gov/vaccines/pregnancy/vaccduring-after.html) and these are now being widely administered in developed countries. This has made the concept of vaccination familiar and acceptable to the majority of pregnant women [71][72][73]. An effective vaccine against GBS would have a number of advantages over the testing and IAP paradigm.…”
Section: Vaccines Against Gbsmentioning
confidence: 99%
“…An initial Glaxo Smith Kline trivalent vaccine that was in phase II trials has been put back into 'discovery' as the results were not 'convincing enough' (https://www.gsk.com/media/5714/ transcript-gsk-vaccines-event-26sep19.pdf). In addition, 55%-85% current vaccine uptakes in pregnancy will need to be improved to make testing no longer necessary [71][72][73]. Other companies such as MinervaX (minervax.com) and Pfizer have also been developing GBS vaccines [77].…”
Section: Vaccines Against Gbsmentioning
confidence: 99%
“…Marked differences in coverage between hospitals were observed; 5 the median influenza vaccination coverage was 45.0% (IQR, 34.7-52.6%; range, 0-75.3%) and 80.4% (IQR, 65.1-86.3%; range; 0-100%) for pertussis vaccination. 5 A 2017 cross-sectional Victorian study that analysed data from 1305 pregnant women, self-reported vaccine uptake was 48.3% for influenza and 82.9% for pertussis 6 and of 1364 South Australian women studied between 2015 and 2017, coverage was 79% and 48% for pertussis and influenza, respectively. 7 Previous studies into understanding antenatal vaccine hesitancy, particularly with respect to influenza and pertussis, have highlighted factors such as concerns about vaccine safety 8,9 and advice from antenatal care providers 10,11 to be influential factors when women are considering antenatal vaccinations.…”
mentioning
confidence: 99%